Representasi Erick Thohir Pada Pemberitaan Bisnis PCR Di Media Online - Maya May Syarah (Prisani Cendekia Institute, 2023)
Abstract:. In choosing news sources, journalists often make someone their favorite source (media darling). This definition refers to sources that journalists like because of their attitudes, actions or statements. Erick Thohir, who has a business background and is now the Minister of BUMN, has emerged as a media darling. However, in November 2021, Erick was reported to the Corruption Eradication Commission (KPK) regarding the PCR business, alleging that Erick was involved in the PCR business. The media is busy reporting on this case. Even though the news about the PCR business comes from the same person, the presentation is always different. There is no such thing as being neutral in reporting, the media will have a different point of view. This is related to certain ideologies embraced by the media (Van Dijk, 1988). For this reason, this research reveals Erick Thohir's representation in reporting on the COVID-19 PCR business case in the online media Republika.co.id and Okezone.com. The aim is to see how the two online media describe representative of Erick Thohir in the PCR business case news. Using Critical Discourse Analysis (CDA) with the Wodak & Reisigl model, the results of the study show that the two online media, namely Republika.co.id and Okezone.com, show Erick as a media darling, as seen from the news that appears depicting the figure of Erick, who is a state official working professionally and well. Everything that is accused by the public can be disputed in the news presented in the online media. The news was conveyed in a positive tone. Even though in the news published on Okezone.com there are sources other than Erick, his statement still represents that Erick is an official who has a good track record.